2017
DOI: 10.1177/2319510x17740043
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Spillovers across Major Emerging Stock Markets

Abstract: Emerging stock markets of Asia have become a matter of interest for international financial researchers and policy-makers during the last couple of decades. Series of reforms, increasing financial transparency and decreasing restrictions on transactions have made these markets better diversification opportunities for international investors. This paper examines independently as well the linkages of stock markets across the selected Asian countries. The volatility spillover is modelled through an asymmetric mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Beirne et al (2013) investigated volatility spillovers and contagion from mature to emerging stock markets using tri-variate GARCH-BEKK models and suggested that spillover parameters change during turbulent while conditional variances in local markets rises, volatility in mature markets rises even much more, and this shift is the main factor behind the increase in conditional correlations. Kumar et al (2018) investigated volatility spillovers across Asian emerging stock markets using an asymmetric multivariate generalized autoregressive conditional heteroscedastic model. The authors concluded that multiple reforms, increasing financial transparency and decreasing restrictions on transactions have transformed these Asian markets into real attractions for international investors in the context of portfolio diversification strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beirne et al (2013) investigated volatility spillovers and contagion from mature to emerging stock markets using tri-variate GARCH-BEKK models and suggested that spillover parameters change during turbulent while conditional variances in local markets rises, volatility in mature markets rises even much more, and this shift is the main factor behind the increase in conditional correlations. Kumar et al (2018) investigated volatility spillovers across Asian emerging stock markets using an asymmetric multivariate generalized autoregressive conditional heteroscedastic model. The authors concluded that multiple reforms, increasing financial transparency and decreasing restrictions on transactions have transformed these Asian markets into real attractions for international investors in the context of portfolio diversification strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Policy makers also have keen interest in studying these patterns in order to stabilise their markets as well as bring in more transparency in the systems. The return potential of emerging markets has compelled global portfolio managers to diversify their portfolios by investing in such markets, such as India, China, South Korea, Malaysia and Taiwan (Kumar et al, 2017). However, due to their interlinkages with other major economies, these Asian markets also take on the threat of the volatility spillovers which may negatively affect the returns of global portfolio managers.…”
Section: Introductionmentioning
confidence: 99%